The Role of the Family in Providing Al-Quran Recitation Therapy to Reduce Anxiety in Elderly People with Hypertension - Yuningsih, Aneng; Marpatmawati, Idhfi; Hertini, Reni (KIAN JOURNAL, 2024)
Introduction: Elderly people with hypertension are at risk of experiencing anxiety due to chronic disease conditions, physical dependence, and psychosocial changes. Al-Qur'an murottal therapy is a potential spiritual approach to reduce anxiety. Family involvement in implementing this therapy at home is an approach that has not been widely explored in the context of religious communities. Objective: This study aims to determine the role of families in providing Al-Qur'an murottal therapy to reduce anxiety in elderly people with hypertension. Method: This study used a qualitative approach with a case study design involving five families in Karang Tengah Hamlet, Balokang Village, Banjar City. Data were collected through semi-structured interviews, participant observation, and measurement of anxiety levels using the Geriatric Anxiety Scale (GAS) before and after therapy. The murottal therapy intervention was carried out by the family for seven consecutive days. Qualitative data were analyzed using thematic analysis techniques, while quantitative data were analyzed descriptively-comparatively. Results: All respondents experienced a decrease in anxiety scores after the intervention, with a score difference between 13 and 30 points. GAS scores showed a decrease from moderate to mild or minimal anxiety categories. Family involvement in guiding and playing murottal consistently strengthens the relaxation effect, sense of security, and emotional support for the elderly and family spiritually, increases the elderly's mental peace, and strengthens affective relationships within the family. Conclusion: Providing murottal Al-Qur'an therapy by families on a regular basis has been proven effective in reducing anxiety levels in elderly people with hypertension. This approach is relevant to be implemented as a community nursing intervention based on spirituality and local culture, especially in religious communities.